Development of the Composition and Technology of New Neuroprotective Drug Tablets Using Fractional Factorial Design - O. A. Terenteva; E. V. Flisyuk; D. Yu. Ivkin; I. A. Narkevich (Разработка и регистрация лекарственных средств)
Introduction. The creating an effective and safe domestic neuroprotective medicines with a complex of pleiotropic effects realized through specific orphan receptors (SUCNR1, HCA2) of glial cells, is a pressing problem of modern pharmacology and a promising possibility of pharmacotherapy of brain injury and cerebrovascular diseases. Ideally, the medicine should helps restore lost cognitive functions and physical performance after damage to the central nervous system, and its use should improve the quality of life of patients and reduce the risk of complications.Aim. To develop composition and technology of a new medicine tablets with neuroprotective effect, using fractional factorial design of experiment and the Harrington desirability function.Materials and methods. The shape and size of particles, physicochemical (solubility, melting point) and technological properties (bulk density, compressibility factor, fractional composition, hygroscopicity) of the pharmaceutical substance of DEAE derivative were studied according to the methods described in the State Pharmacopoeia of the Russian Federation (14th edition). A three-factor fractional plan based on the 4 × 4 Latin square design for selection a scientifically based composition of solid dosage form was chosen. 16 experiments to test the significance of the factors were carried out. The tablets obtained according to the planning matrix were investigated for disintegration; tablet crush resistance, friability, and hygroscopicity. To optimize the quality of the tablets, the generalized Harrington desirability function was used.Results and discussion. The study of the physicochemical and technological properties of the DEAE derivative substance showed that it is a highly hygroscopic, amorphous, white or pale yellow, odourless powder, prone to the formation of agglomerates. The powder is very easily soluble in water. Taking into account the values of the general desirability function, the best result was shown by sample № 4 consisting of mannitol, calcium stearate, and partially pregelatinized maize starch.Conclusion. The physicochemical and technological properties of the DEAE derivative were studied. The DEAE derivative is a highly hygroscopic substance. Via the method of mathematical planning of the experiment the composition of DEAE derivative tablets was selected and scientifically grounded: DEAE derivative 60 mg, mannitol, partially pregelatinized maize starch, calcium stearate. The average tablet weight is 300 mg. The parameters of pressing tablets were selected.